Keunggulan Kompetitif Produk Pangan-Pertanian ASEAN-5 Selama 20 Tahun: Perubahannya Melalui Krisis - Nugraheni, Reninta Dewi; Sabilla, Kanetasya (UI Scholars Hub, 2024)
This study aims to assess the competitive advantage of foreign trade in agri-food products of five Association of South East Asia Nations (ASEAN) countries, namely Indonesia, Malaysia, Thailand, Singapore, and the Philippines between 2003–2022 by dividing the period into the global crisis in 2009, the trade war between China and the United States (US) in 2018, and the COVID-19 pandemic in 2020. The study built an econometric model using the Revealed Comparative Advantage (RCA) and Revealed Symmetric Comparative Advantage (RSCA) indicators. It was found that the value of the RSCA distribution for the five countries has changed significantly over the years of analysis. Shocks in four countries resulted in significant changes in the competitive advantage of agri-food goods. The RSCA distribution results of Singapore and the Philippines could survive compared to other countries in the event of a global economic shock.